Diagnosis and management of hypertension in patients with Cushing's syndrome: a position statement and consensus of the Working Group on Endocrine Hypertension of the European Society of Hypertension. Issue 11 (8th November 2022) - Fallo, Francesco; Di Dalmazi, Guido; Beuschlein, Felix; Biermasz, Nienke R.; Castinetti, Frederic; Elenkova, Atanaska; Fassnacht, Martin; Isidori, Andrea M.; Kastelan, Darko; Korbonits, Márta; Newell-Price, John; Parati, Gianfranco; et al.
Abstract : Endogenous/exogenous Cushing's syndrome is characterized by a cluster of systemic manifestations of hypercortisolism, which cause increased cardiovascular risk. Its biological basis is glucocorticoid excess, acting on various pathogenic processes inducing cardiovascular damage. Hypertension is a common feature in Cushing's syndrome and may persist after normalizing hormone excess and discontinuing steroid therapy. In endogenous Cushing's syndrome, the earlier the diagnosis the sooner management can be employed to offset the deleterious effects of excess cortisol. Such management includes combined treatments directed against the underlying cause and tailored antihypertensive drugs aimed at controlling the consequences of glucocorticoid excess. Experts on endocrine hypertension and members of the Working Group on Endocrine Hypertension of the European Society of Hypertension (ESH) prepared this Consensus document, which summarizes the current knowledge in epidemiology, genetics, diagnosis, and treatment of hypertension in Cushing's syndrome.